THE ANALYSIS OF RISK MITIGATION TECHNIQUE OF HOME FINANCING TAKEOVER IN BANK PANIN DUBAI SYARIAH SURABAYA BRANCH - Firly Aulia Alhimnie; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aims to determine the risk mitigation technique for home financing takeover-funded products. The method used for this research is descriptive qualitative-case study. The data gained from this research is a primary data from an interview with three sources from Panin Dubai Sharia bank, and a secondary data of documentation and financial report of Panin Dubai Sharia Bank. The result of this research is Panin Dubai Sharia bank used reduction mitigation technique either on credit risk or operational risk. On the operational risk, Panin Dubai Sharia bank prepared document takeover and properties takeover further before the contract is done, and implementing Take over Operational Day only on Monday and Thursday. Meanwhile, for credit risk, Panin Dubai Sharia Bank used 4 kinds of systems such as backup of credentials, guarantees, internal ratings, computer models.Keywords: Mitigation, Risk, Take Over, KPRREFFERENCE Arikunto, Suharsimi. (2010). Prosedur penelitian suatu pendekatan praktek. Jakarta: Rineka Cipta.Departemen Agama. (2007). Al Quran dan terjemah. Bandung: PT Sygma Examedia Arkanleema.Flanagan, R. dan Norman, G. (1993). Risk management and construction. Cambridge: University Press.Greuning, Hennie van dan Zamir Iqbal. (2011). Analisis risiko perbankan syariah. Jakarta: Salemba Empat.Karim, Adiwarman. (2010). Bank Islam (Analisis fiqih dan keuangan). Jakarta: PT Raja Grafindo Persada.Khan, Tariqullah dan Habib Ahmed. (2008). Manajemen risiko lembaga keuangan syariah. Jakarta Timur: Sinar Grafika Offset.PT. Bank Panin Dubai Syariah. (2018). Annual report 2018. Jakarta: PT. Bank Panin Dubai Syariah.Sugiyono. (2017). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: CV Alfabeta.Tafsir Al-Mukhtashar/Markaz Tafsir Riyadh. Tafsirweb.com (diakses pada 26 April 2020 pukul 12.48 WIB).Tafsir Quraish Shihab. Tafsirq.com (diakses pada 18 Februari 2020 pukul 7.30 WIB).Tampubolon, Robert. (2004). Risk management. Jakarta: PT. Elex Media Komputindo.Toha, Syarief. (2017). Problematika dalam pelaksanaan pengambilalihan kredit dengan jaminan hak tanggungan. Jurnal Repertorium, 4(2), 95-102.Trisadini P. Usanti dan Abd. Shomad. (2013). Transaksi bank syariah. Jakarta: PT. Bumi Aksara.Yanggo, Chuzaimah T. dan Haifiz Anshary AZ. (1997). Problematika hukum Islam kontemporer. Jakarta: Pustaka Firdaus.Yin, Robert K. (2018). Studi kasus: Desain dan metode. Jakarta: Raja Grafindo Persada.